2021
DOI: 10.1007/s10143-021-01549-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of early failure of VP shunts implanted for hydrocephalus after craniotomies for brain tumors in adults

Abstract: Risks and survival times of ventriculoperitoneal (VP) shunts implanted due to hydrocephalus after craniotomies for brain tumors are largely unknown. The purpose of this study was to determine the overall timing of VP shunting and its failure after craniotomy for brain tumors in adults. The authors also wished to explore risk factors for early VP shunt failure (within 90 days). A population-based consecutive patient cohort of all craniotomies for intracranial tumors leading to VP shunt dependency in adults (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
(94 reference statements)
2
12
0
Order By: Relevance
“…Tumor location was not signi cantly associated with reduced shunt longevity despite dichotomizations into supratentorial/infratentorial and intra-axial/extra-axial tumor location (Table 3). Although somewhat surprising, this is in line with previous studies that did not nd extra-axial/intra-axial tumor location to be signi cantly associated with early shunt-failure after craniotomy for brain tumor [17]. In contrast, Khan et al [24] studied factors affecting shunt survival in adults and found that extra-axial tumors were more common (13.2%) than intra-axial tumors (9.7%), but in line with our results, they reported that brain tumor location was not a signi cant risk factor of shunt failure.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Tumor location was not signi cantly associated with reduced shunt longevity despite dichotomizations into supratentorial/infratentorial and intra-axial/extra-axial tumor location (Table 3). Although somewhat surprising, this is in line with previous studies that did not nd extra-axial/intra-axial tumor location to be signi cantly associated with early shunt-failure after craniotomy for brain tumor [17]. In contrast, Khan et al [24] studied factors affecting shunt survival in adults and found that extra-axial tumors were more common (13.2%) than intra-axial tumors (9.7%), but in line with our results, they reported that brain tumor location was not a signi cant risk factor of shunt failure.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, Hosainey et al [17] studied risk factors of early VP shunt failure after brain tumor surgery and found that patients with pre-existing, non-treated HC prior to craniotomy had a signi cantly shorter shuntfree period before de nitive shunting compared to those without pre-craniotomy HC. Interestingly, in the current study, shunted patients with HC prior to craniotomy had signi cantly longer shunt survival (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the overall median time to shunt failure was shorter in our study as compared to that of Donoho et al [9], but this might be explained by tumor debris and higher protein content in the CSF of patients with brain tumors leading to shunt blockage compared to other non-oncological conditions. Recently, Hosainey et al [17] studied risk factors of early VP shunt failure after brain tumor surgery and found that patients with pre-existing, non-treated HC prior to craniotomy had a significantly shorter shunt-free period before definitive shunting compared to those without precraniotomy HC. Interestingly, in the current study, shunted patients who had HC prior to craniotomy had significantly longer shunt survival (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported a 2% decrease in odds of shunt failure with increasing age at time of shunt insertion [37]. Comparatively, some studies have associated younger age with higher risk of shunt failure [12,37], whereas others have not reached this conclusion regarding age in the shortterm [1,13,17] nor in the long-term period after shunting [24].…”
Section: Discussionmentioning
confidence: 99%